2019
DOI: 10.1111/liv.14220
|View full text |Cite
|
Sign up to set email alerts
|

The systemic inflammatory response as a source of biomarkers and therapeutic targets in hepatocellular carcinoma

Abstract: The pathogenesis of hepatocellular carcinoma (HCC) strongly relates to inflammation, with chronic up‐regulation of pro‐inflammatory mediators standing as a potential unifying mechanism that underscores the origin and progression of HCC independent of aetiology. Activation of the diverse pro‐inflammatory mediators either within the tumour or its microenvironment is part of an active cross‐talk between the progressive HCC and the host, which is known to influence clinical outcomes including recurrence after radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 157 publications
3
57
0
Order By: Relevance
“…Although a large literature already exists on the use of various common blood tests that reflect systemic inflammation and prognosis, and to a lesser extent reflecting in turn the extent of the disease [ [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ], the precise relationship of inflammatory markers to tumor extent has not been well defined. The current work attempts to do this by use of the commonly used PLR and NLR ratios, to assess their relationship to MTD and to try to find their ability to predict small tumor size (MTD).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a large literature already exists on the use of various common blood tests that reflect systemic inflammation and prognosis, and to a lesser extent reflecting in turn the extent of the disease [ [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ], the precise relationship of inflammatory markers to tumor extent has not been well defined. The current work attempts to do this by use of the commonly used PLR and NLR ratios, to assess their relationship to MTD and to try to find their ability to predict small tumor size (MTD).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation-based prognostic scores have been shown to be associated with survival [ 3 ] and with various parameters of tumor aggressiveness [ 4 ]. This may be related to the involvement in tumor growth of a variety of easily measurable indices of inflammation [ 5 ] in routine clinical blood tests, including levels of neutrophils, lymphocytes, monocytes, platelets, albumin, C-reactive protein (CRP), as well as marker ratios, such as albumin and CRP (Glasgow Index), neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) and monocyte-to-lymphocyte ratios, amongst others [ [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ]. In the current study, NLR and PLR were evaluated with reference to maximum tumor diameter (MTD) and also to survival in a large Turkish HCC cohort.…”
Section: Introductionmentioning
confidence: 99%
“…As we all know, inflammation promotes bad prognosis of HCC through induction of thrombocytopenia, lymphopenia, and resistance to chemotherapy (17)(18)(19). Therefore, inflammationbased prediction systems have great potential in predicting the prognosis of HCC patients (7)(8)(9)(10)(11)(12)(13). Especially in China, most cases of HCC are caused by potentially chronic HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is considered as a hallmark of cancer, and more and more evidence has shown that inflammation is closely related to the progression, recurrence, and survival of patients with HCC ( 5 , 6 ). Recently, different inflammation-based scores, such as the Glasgow Prognostic Score (GPS), modified Glasgow Prognostic Score (mGPS), Prognostic Index (PI), Prognostic Nutritional Index (PNI), neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and C-reactive protein/albumin ratio (CAR), have been proposed and been also thought to predict the prognosis of HCC, which mainly calculate quantitative values of plasma neutrophil count, total lymphocyte count, platelet count, albumin level and C-reactive protein (CRP) level, or the ratio or combination between the two indicators; however, those inflammation-based scores are not adequate to predict the overall survival (OS) of HCC patients ( 7 13 ). Besides, to our knowledge, the vast majority of studies on these pretreatment inflammation-based markers have not targeted patients with HCC within the Milan Criteria for ablation therapy.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanism of PAF is still uncertain. It may reflect the degree of hepatic cell damage after loco-regional therapy [33,34] and also reflect a strong inflammatory process that may have roles in anti-tumor immune activity [35]. NLR has also been widely studied in patients with HCC; it is regarded as a predictive factor for survival and it is correlated with some immune dysregulations associated with tumor immune responses [35].…”
Section: Discussionmentioning
confidence: 99%